Lifelong Learning for Career Sustainability: A Grounded Framework for Indian Early Career Engineers - Sangwan, Devika; Venugopal , Abhijith (Journal of Posthumanism, 2025)
The process of becoming an industry-ready engineer does not seem to be an easy task; it involves the acquisition of lifelong learning (LLL) even after placement in the industry. To keep the early career engineers (ECEs) sustainable in the industry, it is essential to know how the ECEs perceive and apply LLL. This study, part of an ongoing research, focuses on the role of LLL in shaping future engineers. This grounded research uses qualitative methods. The data was collected (n=100) from the engineering industry, mainly from early career engineers, managers, and human resource officers, through semi-structured interviews. The results show that LLL, one of the skills most demanded by the industry, was partially used without careful consideration (applicability) by ECEs. The differences in the awareness and use of LLL need more efforts for future-proofing and sustaining their careers as useful work tools. This study signifies the need to acquire feedback from the ECEs, as these active agents would help gather first-hand knowledge, yielding a better understanding, benefiting not only the new entrants but also the industry. The industry will gain a workforce of ECEs capable of contributing directly and effectively through TVCs, optimizing resources like training, mentorship, and digital tools to facilitate seamless integration into Industry 4.0 environments.